2016
DOI: 10.1007/s00709-016-1008-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis and promoter methylation under osmotic and salinity stress of TaGAPC1 in wheat (Triticum aestivum L)

Abstract: Cytosolic glyceraldehyde-3-phosphate dehydrogenase (GAPC) catalyzes a key reaction in glycolysis and encoded by a multi-gene family which showed instability expression under abiotic stress. DNA methylation is an epigenetic modification that plays an important role in gene regulation in response to abiotic stress. The comprehension of DNA methylation at promoter region of TaGAPC1 can provide insights into the transcription regulation mechanisms of plant genes under abiotic stress. In this study, we cloned TaGAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 51 publications
1
15
0
1
Order By: Relevance
“…This genotype specific high level of DNA methylation is in accordance with the previous reports where DNA hypermethylation has been observed stress responsive genes under control conditions. In a recent study, high level of DNA methylation was revealed in ABRERATCAL and MYB-core cis-regulatory elements of the promoter region of TaGAPC1 in wheat (Fei et al 2017). Similar to our results, the relatively more tolerant wheat genotype showed higher level of DNA methylation under normal conditions.…”
Section: Discussionsupporting
confidence: 91%
“…This genotype specific high level of DNA methylation is in accordance with the previous reports where DNA hypermethylation has been observed stress responsive genes under control conditions. In a recent study, high level of DNA methylation was revealed in ABRERATCAL and MYB-core cis-regulatory elements of the promoter region of TaGAPC1 in wheat (Fei et al 2017). Similar to our results, the relatively more tolerant wheat genotype showed higher level of DNA methylation under normal conditions.…”
Section: Discussionsupporting
confidence: 91%
“…In wheat, the expression pattern of TaGAPC1 was regulated under osmotic and salinity stress conditions. The promoter region of TaGAPC1 contains various stress-related cis -regulatory elements (including MBS, DRE, GT1, and LTR), and methylation changes were observed during the stress treatments, leading to stress tolerance and regulation in gene expression ( Fei et al, 2017 ). In the current study, these results were further authenticated by the GO annotation evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Improving the quality and biotic/abiotic resistances of crops has become a topic of considerable interest throughout the world. Progress in breeding biotic and abiotic stress-resistant crops and developing biotic and abiotic stress resistance-inducing reagents, especially oligosaccharide-like, environmentally friendly reagents, has been achieved (Thomashow, 1999; Dzung et al ., 2011; Liu et al ., 2013; Sun et al ., 2013; Qiang et al ., 2015; Jing et al ., 2016; Fei et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%